Improving Public Perceptions of Dairy Production Through On-Farm Educational Tours - Drew Swartz; Justin Wyatt Clawson; Jaydee Gunnell; Elise Jenson; Dylan Waldron; Jenna Dyckman (Outcomes and Impact Quarterly, 2026)
Utah dairy producers identified public perceptions as a top concern. Utah State University Extension partnered with Cache County organizations to offer dairy farm tours. Participants reported increased knowledge, more favorable perceptions, and stronger intentions to engage with agriculture, supporting experiential education as a means to strengthen understanding of dairy production.